Hypoxia and exercise: different models for different questions - Sheel, A. W. (Applied Physiology, Nutrition, and Metabolism, 2008)
The focus of this symposium is on the physiological demands of exercise in hypoxia. The study of hypoxia by exercise physiologists has a strong tradition and many questions first asked over 100 years ago continue to be relevant, yet still unsatisfactorily answered. The primary theme of the following papers is how different models of hypoxia allow different questions to be asked. The first paper addresses questions of exercise ventilatory control using intermittent, rather than continuous, hypoxia. The second manuscript attempts to understand the hypoxic exercise responses using a population-level approach (i.e., generations spanning millennia). Lastly, the third paper uses acute hypoxia to better understand cardio-pulmonary interactions during exercise. Collectively, these reviews are intended to stimulate additional study and debate.